O processo democrático no município de ponta grossa: uma análise sobre a produção legislativa e a participação da sociedade civil (2013-2016) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This research propose is identify the existence of civil society participation in the democratic debate in Ponta Grossa between the years 2013 and 2016 regarding participation in the legislative process. To begin the discussion, this study presents a historical context about the different conceptions of democracy, showing the reader why the Gramscian conception was adopted. Then, the historical demonstration of political, economic and social issues from Brazil colônia was set, the reason is identify the influences, ideologies and events that contributed to the current formation of the State. Considering the method that has been used in the research, it was tried to demonstrate the totality, the existence of contradictions and especially the existence of the class struggle. The definition of civil society, political society, passive revolution, directing and been directed were the main categories that stitched together the theoretical referential to the studied reality. After the theoretical definition of these categories (and some more),was analyzed the social composition of the city of Ponta Grossa. For that, it was demonstrated how it was constituted, how civil society was formed and what were the ideologies that promoted the formation of the city. Considering that the general objective was to analyze the democratic participation of civil society in the legislative process in the period 2013-2016, it was demonstrated who composes the civil society of Ponta Grossa and the significant number of institutions that exer t influence in political, economic and social aspects. After this demonstration, the document analysis and content analysis technique was used to quantify the number of bills proposed during the period, in order to find in its justifications some civil society participation. However, was possible to conclude that even if exists a civil society with diferent people and institutuions, in the analysis it has not been possible to identify the civil society participation in the legislative process.
Keywords: Sociedade civil; Democracia; Hegemonia; Gramsci; Processo legislativo.; Civil society; Democracy; Hegemony; Gramsci; Legislative process; CNPQ::CIENCIAS SOCIAIS APLICADAS